Protein Tyrosine Phosphatases in Cancer - Neel, Benjamin G.; Tonks, Nicholas K. (Springer New York : Imprint: Springer, 2016)
This book aims to bridge the gap in understanding how protein-tyrosine phosphatases (PTPs), which carry out the reverse reaction of tyrosine phosphorylation, feature in cancer cell biology. The expertly authored chapters will first review the general features of the PTP superfamily, including their overall structure and enzymological properties; use selected examples of individual PTP superfamily members, to illustrate emerging data on the role of PTPs in cancer; and will review the current status of PTP-based drug development efforts. Protein Tyrosine Phosphatases in Cancer,from renowned researchers Benjamin Neel and Nicholas Tonks, is invaluable reading for researchers in oncology, stem cell signaling,and biochemistry. .